2019
DOI: 10.1038/s41598-019-51933-z
|View full text |Cite
|
Sign up to set email alerts
|

Shear-induced microstructures and dynamics processes of phospholipid cylinders in solutions

Abstract: Shear-induced microstructures and their corresponding dynamic processes are investigated for phospholipid cylinders in aqueous solution by dissipative particle dynamic simulation. Various phospholipid cylinders with cross-sections, which are formed under shear-free flow, are selected to examine the effects of shear flow on their structures and dynamic processes. Shear flow induces the transition from cylinders into vesicles at weak rate and the transition into vesicle–lamella mixtures with increased shear rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 67 publications
(78 reference statements)
0
7
1
Order By: Relevance
“…The relaxation sustained a longer time in the strong adsorption cases compared with the weak adsorption case. The variance in the shape factor of a single bottlebrush molecule is different from those in previous works [ 42 ], in which the shape factor had undergone a process of first decreasing and then increasing, which is contrary to our results.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…The relaxation sustained a longer time in the strong adsorption cases compared with the weak adsorption case. The variance in the shape factor of a single bottlebrush molecule is different from those in previous works [ 42 ], in which the shape factor had undergone a process of first decreasing and then increasing, which is contrary to our results.…”
Section: Resultscontrasting
confidence: 99%
“…The gyration radius is an important parameter to understand the polymer size in the dynamic process [ 42 ]. The average radius of gyration can be defined as follows: …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is evidence that shape factor hdi begins at 0.47 and then approaches 0.5 at the stable stage, a result that is similar to previous simulation results. 64 To observe the shape factor in detail, we drew the variation of the shape factor between 0s and 500s as the inserted part. By investigating the variation of the shape factor, we found that the asymmetric vesicle structure easily forms when the structure of the single chain exhibits spherical conformation.…”
Section: Dynamic Processmentioning
confidence: 99%
“…When a complex fluid is subject to shear, a novel structure can emerge. Recent studies include for lamellar phases [17], colloids [18][19][20][21], colloidal gels [22][23][24], star polymers [25,26], biomolecules [27][28][29][30], biofluids [31], hydrogels [32], and graphene particles [33,34]. Neutron and x-ray scattering methods have proven valuable probes of the structure and rheology in soft matter [16,26,28,[35][36][37][38][39][40][41].…”
mentioning
confidence: 99%